2002
DOI: 10.1248/bpb.25.239
|View full text |Cite
|
Sign up to set email alerts
|

Differential mRNA Expression of Inflammatory Cytokines in Cultured Human Fetal Membrane Cells Responding to Influenza Virus Infection.

Abstract: When a virus encounters a susceptible cell, the virus enters and initiates cytocidal, persistent, latent or abortive infection. We recently reported that influenza virus (IV) induces persistent infection accompanied by cell survival and virus production in cultured amnion cells. In addition, cytocidal infection accompanied by apoptotic cell death and virus production occurred in cultured chorion cells. Both cell cultures were prepared from human fetal membranes. 1)IV induces cytocidal infection in a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 33 publications
2
34
3
Order By: Relevance
“…Interestingly, we have reported that influenza virus infection induced apoptosis and the gene expression of interleukin (IL)-6, tumor necrosis factor (TNF)-α and interferon (IFN)-β in cultured human fetal membrane chorion trophoblast cells. [12][13][14] However, even though the virus proliferated in cultured amnion epithelial cells, it should be noted that we did not observe the above phenomena in these cells. [12][13][14] Overall, these findings suggest that the induction of apoptosis and gene expression of pro-inflammatory cytokines in chorion trophoblast cells may have a possible role in the etiology of adverse pregnancy outcomes that are associated with an intrauterine infection caused by an influenza virus.…”
contrasting
confidence: 68%
See 2 more Smart Citations
“…Interestingly, we have reported that influenza virus infection induced apoptosis and the gene expression of interleukin (IL)-6, tumor necrosis factor (TNF)-α and interferon (IFN)-β in cultured human fetal membrane chorion trophoblast cells. [12][13][14] However, even though the virus proliferated in cultured amnion epithelial cells, it should be noted that we did not observe the above phenomena in these cells. [12][13][14] Overall, these findings suggest that the induction of apoptosis and gene expression of pro-inflammatory cytokines in chorion trophoblast cells may have a possible role in the etiology of adverse pregnancy outcomes that are associated with an intrauterine infection caused by an influenza virus.…”
contrasting
confidence: 68%
“…[12][13][14] However, even though the virus proliferated in cultured amnion epithelial cells, it should be noted that we did not observe the above phenomena in these cells. [12][13][14] Overall, these findings suggest that the induction of apoptosis and gene expression of pro-inflammatory cytokines in chorion trophoblast cells may have a possible role in the etiology of adverse pregnancy outcomes that are associated with an intrauterine infection caused by an influenza virus. 5,15) The main etiological factor responsible for the development of both premature rupture of the membranes (PROM) and preterm labor has been reported to be an intrauterine bacterial infection.…”
contrasting
confidence: 68%
See 1 more Smart Citation
“…7,8) While the relationship of viral replication in host cells to host cell apoptosis has been definitely shown, the role of virus contact with host cell surface as the stimulus to induce apoptosis has not been examined previously. We know that the viral surface components which have direct contact with the host cell surface are neuraminidase, hemagglutinin and membrane protein-2, however, the participation of these viral components in the induction of host cell apoptosis has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…1) Chorion trophoblast cells expressed significantly amounts of inflammatory cytokine gene mRNAs in response to IV infection, such as interleukin (IL)-1b, IL-6, tumor necrosis factor (TNF)-a, interferon (IFN)-b, IFN-g, granulocyte macrophage colony-stimulating factor (GM-CSF) and Fas antigen, however, these cytokines production was not directly related to the apoptosis induction. 2) Thus, we speculate that the expression of these inflammatory cytokines may be related to set up the antiviral response system in the maternal body.…”
mentioning
confidence: 91%